Statistics “in Relation to Themselves”: African American Activists, the Census of 1840, and the Radical Potential of Quantification - Wierda, Meagan (Journal of the Early Republic, 2025)
This article recovers the overlooked role of quantification in shaping antebellum Black knowledge claims about freedom and slavery. It uses the political controversy surrounding the census of 1840 to highlight the extent to which African American activists in New York City rooted a pro-Black and anti-slavery politics in the growing authority of numbers. Owing to a series of clerical errors, the disputed sixth decennial census—the first to solicit the number of individuals designated as “insane” or “idiots” throughout the population—indicated that African Americans in the North were far more likely to suffer from “insanity” than their counterparts in the South. Unsurprisingly, exultant pro-slavery ideologues wasted no time in adding the census to their growing repertoire of evidence supporting the peculiar institution. Black New Yorkers, however, understood that the conclusions drawn from the census were a product of a racist statistical practice, and not a true reflection of either Black freedom or of quantification’s radical potential. Using an 1844 memorial to the United States Senate produced by Black activists in New York City, this article argues that African Americans were resourceful quantifiers who strategically employed quantitative arguments to dispute the claim that Blackness was incompatible with freedom. Indeed, close study of the memorial reveals the extent to which activists’ use of quantification to undermine pro-slavery expansionism, represent slavery’s fatal violence, and affirm the degree to which they were thriving in freedom is indicative of a much more robust and underappreciated culture of numeracy among antebellum African Americans.
Keywords: =CL; Abolition; Activism; African Americans; Census; Data; Disability; James McCune Smith; New York; Numeracy; Quantification; Slavery; Statistics

Population Projections: Demographic Fearmongering and “Uterine Colonization” during the Age of Gradual Emancipation - Wierda, Meagan (Journal for the History of Knowledge, 2025)
Centered primarily on the American Colonization Society (ACS), this article explores the movement to colonize free Black women and men in West Africa as a political—as well as a knowledge—project rooted in demography. Hostile to slavery and immediate emancipation alike, white colonizationists used quantitative rhetoric to transform African Americans along a vast spectrum of unfreedom into a “dangerous” and multiplying population in need of removal. While this demographic fearmongering proved effective, the ACS struggled to make large-scale expatriation appear equally so. To render removal “practicable,” colonizationists harnessed the fertility of African American women. By specifically targeting those in their procreative prime for expatriation, colonizationists believed they could gradually deplete the country’s Black population. The colonization project as envisioned by the ACS, then, was the clear inheritor of demography’s hierarchizing tendencies. Not only did colonizationists reproduce the epistemic violence of a system that fragmented and instrumentalized the bodies of Black women, but in specifically targeting the latter for expatriation, they produced a new category via which to define African Americans as a threatening and unassimilable population.
Keywords: =CL; American Colonization Society; demography; gender; population; race; slavery

“Hell No, Our Genes Aren’t Slow!”: Racism and Antiracism at Rutgers during the 1995 Controversy - Wierda, Meagan; Orozco, Roberto C. (Scarlet and Black, Volume Three: Making Black Lives Matter at Rutgers, 1945-2020, 2021)
The 250th anniversary of the founding of Rutgers University is a perfect moment for the Rutgers community to reconcile its past, and acknowledge its role in the enslavement and debasement of African Americans and the disfranchisement and elimination of Native American people and culture. Scarlet and Black, Volume Three, concludes this groundbreaking documentation of the history of Rutgers’s connection to slavery, which was neither casual nor accidental—nor unusual. Like most early American colleges, Rutgers depended on slaves to build its campuses and serve its students and faculty; it depended on the sale of black people to fund its very existence. This final of three volumes concludes the work of the Committee on Enslaved and Disenfranchised Population in Rutgers History. This latest volume includes essays about Black and Puerto Rican students' experiences; the development of the Black Unity League; the Conklin Hall takeover; the divestment movement against South African apartheid; anti-racism struggles during the 1990s; and the Don Imus controversy and the 2007 Scarlet Knights women's basketball team. To learn more about the work of the Committee on Enslaved and Disenfranchised Population in Rutgers History, visit the project's website at http://scarletandblack.rutgers.edu.
Keywords: Education / History; Education / Schools / Levels / Higher; History / General; History / United States / 20th Century; History / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA); Social Science / Discrimination; Social Science / Indigenous Studies; _AV

From the Classroom to the American Colonization Society: Making Race at Rutgers - Adams, Beatrice; Johnson, Tracey; Manuel, Daniel; Wierda, Meagan (Scarlet and Black, Volume One: Slavery and Dispossession in Rutgers History, 2016)
“Citizens of New-Jersey,” exhorted Theodore Frelinghuysen, a fellow New Jerseyan, at an 1824 meeting of the state’s colonization society, “—we appeal to you—survey your cultivated fields—your comfortable habitations—your children rising around you to bless you. Who, under Providence, caused those hills to rejoice, and those vallies to smile?—who ploughed those fields and cleared those forests?” His answer may have come as a surprise to some, as he demanded that his audience “remember the toil and the tears of black men, and pay [their] debt to Africa.”¹ According to Frelinghuysen, the people of New Jersey owed
Keywords: _AV

All the World's a Classroom: The First Black Students Encounter the Racial, Religious, and Intellectual Life of the University - Johnson, Tracey; Kitada, Eri; Wierda, Meagan; Williams, Joseph (Scarlet and Black, Volume Two: Constructing Race and Gender at Rutgers, 1865-1945, 2020)
The 250th anniversary of the founding of Rutgers University is a perfect moment for the Rutgers community to reconcile its past, and acknowledge its role in the enslavement and debasement of African Americans and the disfranchisement and elimination of Native American people and culture. Scarlet and Black, Volume 2, continues to document the history of Rutgers’s connection to slavery, which was neither casual nor accidental—nor unusual. Like most early American colleges, Rutgers depended on slaves to build its campuses and serve its students and faculty; it depended on the sale of black people to fund its very existence. This second of a planned three volumes continues the work of the Committee on Enslaved and Disenfranchised Population in Rutgers History. This latest volume includes: an introduction to the period studied (from the end of the Civil War through WWII) by Deborah Gray White; a study of the first black students at Rutgers and New Brunswick Theological Seminary; an analysis of African-American life in the City of New Brunswick during the period; and profiles of the earliest black women to matriculate at Douglass College. To learn more about the work of the Committee on Enslaved and Disenfranchised Population in Rutgers History, visit the project's website at http://scarletandblack.rutgers.edu
Keywords: Education / History; Education / Schools / Levels / Higher; History / General; History / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA); Social Science / Discrimination; Social Science / Ethnic Studies / American / African American & Black Studies; Social Science / Ethnic Studies / American / Native American Studies; Social Science / Slavery; Social Science / Women's Studies; _AV